Inorganic nano-composite coating material applied to corrosion prevention of splash zone and preparation method of inorganic nano-composite coating material
By using technical means of using inorganic nanocomposite coating materials in anticorrosion coatings in the waves and splash areas, the problems of poor impact resistance and insufficient corrosion resistance of anticorrosion coatings in the prior art are solved, and the coating materials are rapidly cured, with strong adhesion, impact resistance and corrosion resistance at room temperature.
Patent Information
- Application Number
- CN202411867489.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, the anti-corrosion coating used in the wave splash zone has poor impact resistance and insufficient corrosion resistance. Especially under the impact of huge waves, the coating is prone to fracture, resulting in weakening of corrosion resistance.
Using an inorganic nanocomposite coating material, a modified liquid epoxy resin is formed by graft polymerization reaction between dodecyl methacrylate, dimethyl vinyl phosphate and dibenzoyl peroxide and liquid epoxy resin, and mixed with end carboxylic liquid nitrile rubber and polypropylene glycol diglycidyl ether to form component A; at the same time, a component B is mixed with amino modified nanosilica and a curing agent to form component B, and finally a component A and component B are mixed in a ratio of 2:1 to prepare a coating material with excellent adhesion, toughness and anti-corrosion properties.
The coating material cures quickly at room temperature, has strong adhesion, has good impact resistance and corrosion resistance, can effectively resist the impact of ocean waves and extend the service life of the steel structure.
Smart Images

Figure CN119529633A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to an inorganic nano-composite coating material used for corrosion protection in splash zones and a preparation method thereof. Background Art
[0002] The marine environment is extremely corrosive to steel structures, affecting their service life. The splash zone is the most corrosive area in the marine environment. The sufficient oxygen supply and the huge impact of the waves will accelerate the corrosion of steel structures. Coating is an effective means of metal corrosion protection. Among them, organic coatings are prone to aging, powdering, and low adhesion on metal surfaces, so they have a short lifespan and need to be repainted frequently. Therefore, it is necessary to add organic nanomaterials to enhance the anti-corrosion performance of coating materials.
[0003] Chinese patent CN108841289B discloses a method for preparing a long-lasting anticorrosive and weather-resistant functional coating, the components of which include: bisphenol A epoxy resin, solvent, nano titanium-based hybrid material, mica powder and talcum powder, defoamer, plasticizer, leveling agent and epoxy curing agent, organic polymer and nano inorganic small molecule combination, good anticorrosive performance. However, the compatibility and dispersion uniformity between inorganic materials and epoxy resin need to be improved, and the anticorrosive performance needs to be improved. In addition, epoxy resin is brittle after curing. Under the impact of huge waves, the coating is prone to breakage and the anticorrosive performance is weakened. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention provides an inorganic nano-composite coating material for use in splash zone corrosion protection, so as to solve the problems of poor impact resistance and corrosion resistance of the prior art anti-corrosion coatings for splash zone.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] An inorganic nanocomposite coating material for splash zone corrosion protection includes a component A and a component B, and is prepared by the following method:
[0007] Step 1, adding dodecafluoroheptyl methacrylate, dimethyl vinyl phosphate and dibenzoyl peroxide into ethyl acetate, stirring and dispersing to obtain a mixed solution;
[0008] Add liquid epoxy resin to ethyl acetate, stir and disperse, raise the temperature to a set temperature under the protection of inert gas, drop the mixed solution, react after the dropwise addition, and rotary evaporate after the reaction to obtain a modified liquid epoxy resin;
[0009] Step 2: Mix the modified liquid epoxy resin and the carboxyl-terminated liquid nitrile rubber, react, cool to room temperature after the reaction, add polypropylene glycol diglycidyl ether, stir, and obtain component A;
[0010] The amino-modified nano-silica is mixed with the curing agent and stirred to obtain component B;
[0011] Wherein, the curing agent is prepared by the following steps:
[0012] Aliphatic polyamine and dicyclohexylcarbodiimide are stirred, and then oleic acid is added to react. After the reaction is completed, the reaction is purified to obtain a curing agent.
[0013] Preferably, in step 1: when preparing the mixed solution, the mass ratio of dodecafluoroheptyl methacrylate, dimethyl vinyl phosphate, dibenzoyl peroxide and ethyl acetate is (35-45):(13-16):(5-7):(200-300).
[0014] Preferably, in the step 1: when preparing the modified liquid epoxy resin, the mass ratio of the liquid epoxy resin, ethyl acetate and the mixed liquid is (850-1000):(500-750):(500-700), and the dripping time of the mixed liquid is 40-60 min.
[0015] Preferably, in the step 1, the reaction conditions are to react for 3-4 hours at a set temperature under the protection of an inert gas, and the set temperature is 100-120°C.
[0016] Preferably, the inert gas comprises nitrogen.
[0017] Preferably, in the step 2: when preparing component A, the mass ratio of the modified liquid epoxy resin, the carboxyl-terminated liquid nitrile rubber, and the polypropylene glycol diglycidyl ether is (900-1060):(150-170):(200-250), and the reaction conditions are to react at a temperature of 140-160°C for 2.5-3.5h; and the stirring conditions are to stir at a stirring speed of 250-350r / min for 40-60min.
[0018] Preferably, in the step 2: when preparing component B, the mass ratio of amino-modified nano-silica to curing agent is (66-70):(380-460), and the stirring condition is stirring at a stirring speed of 150-250 r / min for 40-60 min.
[0019] Preferably, the component A and the component B prepared in step 2 are mixed and stirred before use, the stirring condition is stirring at a stirring speed of 250-350 r / min for 3-5 min, and the mass ratio of component A to component B is 2:1.
[0020] Preferably, the amino-modified nano-silica in step 2 is prepared by the following steps:
[0021] N-2-aminoethyl-3-aminopropyltrimethoxysilane is added to an ethanol aqueous solution, the pH value is adjusted to 3-5, nano-silicon dioxide is added, and the reaction is carried out. After the reaction is completed, the reaction is filtered, washed, and dried to obtain amino-modified nano-silicon dioxide.
[0022] Preferably, the mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane, ethanol aqueous solution and nano-silicon dioxide is (50-70):(250-350):60, and the reaction conditions are 60-80° C. for 3-5 hours.
[0023] Preferably, the ethanol aqueous solution comprises 90 wt % ethanol aqueous solution.
[0024] Preferably, in step 2: when preparing the curing agent, the molar ratio of aliphatic polyamine, dicyclohexylcarbodiimide and oleic acid is (1.1-1.5):1:(1-1.3), and the reaction conditions are under the protection of an inert gas and at a temperature of 30-50° C. for 3-5 hours.
[0025] Preferably, the aliphatic polyamine comprises triethylenetetramine.
[0026] The present invention also discloses an inorganic nano-composite coating material for anti-corrosion in a splash zone, which is prepared by the above-mentioned method for preparing the inorganic nano-composite coating material for anti-corrosion in a splash zone.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] In the present invention, liquid epoxy resin is used as the film-forming material of the composite coating material, which has good adhesion and anti-corrosion performance. The introduction of organic fluoride dodecafluoroheptyl methacrylate can improve the hydrophobicity of the composite coating material. The introduction of organic phosphate vinyl dimethyl phosphate can improve the adhesion of the composite coating material. The introduction of organic toughening material terminal carboxyl liquid nitrile rubber can improve the toughness of the composite coating material, thereby improving the ability of the coating to resist the impact of waves. Adding polypropylene glycol diglycidyl ether as an epoxy resin active diluent can not only dilute the epoxy resin and avoid the pollution of the water environment caused by the use of organic solvents, but also participate in the curing reaction through the epoxy groups at both ends of the molecule, and its flexible molecular chain can also improve the toughness of the composite coating material.
[0029] In the present invention, when preparing component A, dodecafluoroheptyl methacrylate and vinyl dimethyl phosphate undergo graft polymerization reaction with liquid epoxy resin under the action of dibenzoyl peroxide as an initiator to obtain modified liquid epoxy resin, and organic fluoride and organic phosphate are connected to the epoxy resin molecular chain with stable chemical bonds; the modified liquid epoxy resin undergoes a ring-opening reaction with the carboxyl group at the end of the carboxyl-terminated liquid nitrile rubber, and the organic toughening material is connected to the epoxy resin molecular chain with a stable chemical bond, the compatibility and dispersion uniformity between the organic fluoride, the organic phosphate, the organic toughening material and the epoxy resin are good, and the coating material has stable performance;
[0030] In the present invention, when preparing component B, the curing agent is prepared by reacting aliphatic polyamine with oleic acid. The curing agent molecule contains amide groups and fatty polyamines. The fatty polyamines have high reactivity with epoxy groups and can react with epoxy resins at room temperature to rapidly cure the epoxy resins. The introduction of oleic acid molecular chains can also improve the toughness of the coating. The inorganic nanomaterial-nano silicon dioxide is introduced. The "maze effect" generated by the inorganic nanoparticles can effectively extend the corrosion path, reduce the corrosion rate, and improve the protective performance of the coating. In addition, the inorganic nanomaterial can also improve the strength and toughness of the coating. The nano silicon dioxide is subjected to amino modification treatment, and the introduced fatty amine can also participate in the curing and cross-linking reaction of the epoxy resin, further improving the strength of the coating.
[0031] The composite coating material prepared by the invention can be quickly solidified at room temperature, has strong adhesion and strong hydrophobicity, and can realize water-carrying operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a process flow chart for preparing the inorganic nanocomposite coating material used for splash zone corrosion protection in the present invention;
[0033] Figure 2 It is a line graph of the test results of the curing and drying time of the composite coating materials prepared in Examples 1-6 of the present invention and Comparative Examples 1-2;
[0034] Figure 3 It is a line graph of adhesion test results of coatings formed after curing and drying of the composite coating materials prepared in Examples 1-6 of the present invention and Comparative Examples 1-2;
[0035] Figure 4 It is a line chart of the impact resistance test results of the coatings formed after curing and drying of the composite coating materials prepared in Examples 1-6 of the present invention and Comparative Examples 1-2;
[0036] Figure 5 It is a line graph showing the test results of the neutral salt spray resistance of the steel plates coated with the composite coating materials prepared in Examples 1-6 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION
[0037] Example 1
[0038] This embodiment discloses a method for preparing an inorganic nanocomposite coating material for anti-corrosion in a splash zone, comprising the following steps:
[0039] Step 1, adding dodecafluoroheptyl methacrylate, vinyl dimethyl phosphate, and dibenzoyl peroxide to ethyl acetate, wherein the mass ratio of dodecafluoroheptyl methacrylate, vinyl dimethyl phosphate, dibenzoyl peroxide, and ethyl acetate is 35:13:5:200, and stirring and dispersing at a stirring speed of 150 r / min for 30 minutes to obtain a mixed solution;
[0040] Add liquid epoxy resin to ethyl acetate, stir and disperse at a stirring speed of 150r / min for 30min, and then heat to 100°C under nitrogen protection, and drop the mixed solution. The mass ratio of liquid epoxy resin, ethyl acetate and mixed solution is 850:500:500. The dropwise addition time of the mixed solution is 40min. After the dropwise addition is completed, react at 100°C for 4h under nitrogen protection. After the reaction is completed, remove ethyl acetate by rotary evaporation at 55°C to obtain a modified liquid epoxy resin;
[0041] Step 2: Mix the modified liquid epoxy resin and the carboxyl-terminated liquid nitrile rubber, react at 140° C. for 3.5 hours, cool to room temperature after the reaction, add polypropylene glycol diglycidyl ether, the mass ratio of the modified liquid epoxy resin, the carboxyl-terminated liquid nitrile rubber, and the polypropylene glycol diglycidyl ether is 900:150:200, stir at a stirring speed of 150 r / min for 60 minutes, and obtain component A;
[0042] The amino-modified nano-silica and the curing agent are mixed, the mass ratio of the amino-modified nano-silica to the curing agent is 66:380, and the mixture is stirred at a stirring speed of 150 r / min for 60 min to obtain component B;
[0043] Wherein, the amino-modified nano-silica is prepared by the following steps:
[0044] Add N-2-aminoethyl-3-aminopropyltrimethoxysilane to a 90wt% ethanol aqueous solution, add 1mol / L acetic acid aqueous solution to adjust the pH value to 3, add nano-silica, the mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane, ethanol aqueous solution, and nano-silica is 50:250:60, react at 60°C for 5h, filter after the reaction, wash with ethanol 3 times, and dry in a 50°C vacuum drying oven for 24h to obtain amino-modified nano-silica;
[0045] The curing agent is prepared by the following steps:
[0046] Triethylenetetramine and dicyclohexylcarbodiimide were stirred at a stirring speed of 150 r / min for 30 min, and then oleic acid was added, the molar ratio of triethylenetetramine, dicyclohexylcarbodiimide and oleic acid was 1.1:1:1, and the mixture was reacted at 30°C for 5 h under nitrogen protection. After the reaction was completed, 10 times the mass of tetrahydrofuran at 0°C was added to the reaction mixture, and the mixture was stirred at a stirring speed of 150 r / min for 30 min, and then filtered. The filtrate was rotary evaporated at 35°C to remove tetrahydrofuran to obtain a curing agent;
[0047] Component A and component B are mixed and stirred before use. The stirring condition is stirring at a stirring speed of 250 r / min for 5 minutes. The mass ratio of component A to component B is 2:1.
[0048] Example 2
[0049] This embodiment discloses a method for preparing an inorganic nanocomposite coating material for anti-corrosion in a splash zone, comprising the following steps:
[0050] Step 1, adding dodecafluoroheptyl methacrylate, dimethyl vinyl phosphate, and dibenzoyl peroxide to ethyl acetate, wherein the mass ratio of dodecafluoroheptyl methacrylate, dimethyl vinyl phosphate, dibenzoyl peroxide, and ethyl acetate is 45:16:7:300, and stirring and dispersing at a stirring speed of 150 r / min for 30 minutes to obtain a mixed solution;
[0051] Add liquid epoxy resin to ethyl acetate, stir and disperse for 30 minutes at a stirring speed of 150r / min, and then heat to 120°C under nitrogen protection, and drop the mixed solution. The mass ratio of liquid epoxy resin, ethyl acetate and mixed solution is 1000:750:700. The dropwise addition time of the mixed solution is 60 minutes. After the dropwise addition is completed, react at 120°C for 3 hours under nitrogen protection. After the reaction is completed, remove ethyl acetate by rotary evaporation at 55°C to obtain a modified liquid epoxy resin;
[0052] Step 2: Mix the modified liquid epoxy resin and the carboxyl-terminated liquid nitrile rubber, react at 160° C. for 2.5 hours, cool to room temperature after the reaction, add polypropylene glycol diglycidyl ether, the mass ratio of the modified liquid epoxy resin, the carboxyl-terminated liquid nitrile rubber, and the polypropylene glycol diglycidyl ether is 1060:170:250, stir at a stirring speed of 250 r / min for 40 minutes, and obtain component A;
[0053] The amino-modified nano-silica and the curing agent are mixed, the mass ratio of the amino-modified nano-silica to the curing agent is 70:460, and the mixture is stirred at a stirring speed of 250 r / min for 40 minutes to obtain component B;
[0054] Wherein, the amino-modified nano-silica is prepared by the following steps:
[0055] Add N-2-aminoethyl-3-aminopropyltrimethoxysilane to a 90wt% ethanol aqueous solution, add 1mol / L acetic acid aqueous solution to adjust the pH value to 5, add nano-silica, the mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane, ethanol aqueous solution, and nano-silica is 70:350:60, react at 80°C for 3h, filter after the reaction, wash with ethanol 3 times, and dry in a 50°C vacuum drying oven for 24h to obtain amino-modified nano-silica;
[0056] The curing agent is prepared by the following steps:
[0057] Triethylenetetramine and dicyclohexylcarbodiimide were stirred at a stirring speed of 150 r / min for 30 min, and then oleic acid was added, the molar ratio of triethylenetetramine, dicyclohexylcarbodiimide and oleic acid was 1.5:1:1.3, and the mixture was reacted at 50°C for 3 h under nitrogen protection. After the reaction was completed, 10 times the mass of tetrahydrofuran at 0°C was added to the reaction mixture, and the mixture was stirred at a stirring speed of 150 r / min for 30 min, and then filtered. The filtrate was rotary evaporated at 35°C to remove tetrahydrofuran to obtain a curing agent;
[0058] Component A and component B are mixed and stirred before use. The stirring condition is stirring at a stirring speed of 350 r / min for 3 minutes. The mass ratio of component A to component B is 2:1.
[0059] Example 3
[0060] This embodiment discloses a method for preparing an inorganic nanocomposite coating material for anti-corrosion in a splash zone, comprising the following steps:
[0061] Step 1, adding dodecafluoroheptyl methacrylate, vinyl dimethyl phosphate, and dibenzoyl peroxide to ethyl acetate, wherein the mass ratio of dodecafluoroheptyl methacrylate, vinyl dimethyl phosphate, dibenzoyl peroxide, and ethyl acetate is 37:13.5:5.5:220, and stirring and dispersing at a stirring speed of 150 r / min for 30 minutes to obtain a mixed solution;
[0062] Add liquid epoxy resin to ethyl acetate, stir and disperse for 30 minutes at a stirring speed of 150r / min, and then heat to 110°C under nitrogen protection, and drop the mixed solution. The mass ratio of liquid epoxy resin, ethyl acetate and mixed solution is 880:550:550. The dropwise addition time of the mixed solution is 50 minutes. After the dropwise addition is completed, react at 110°C for 3.5 hours under nitrogen protection. After the reaction is completed, remove ethyl acetate by rotary evaporation at 55°C to obtain a modified liquid epoxy resin;
[0063] Step 2: Mix the modified liquid epoxy resin and the carboxyl-terminated liquid nitrile rubber, react at 150° C. for 3 hours, cool to room temperature after the reaction, add polypropylene glycol diglycidyl ether, the mass ratio of the modified liquid epoxy resin, the carboxyl-terminated liquid nitrile rubber, and the polypropylene glycol diglycidyl ether is 935:155:210, stir at a stirring speed of 300 r / min for 50 minutes, and obtain component A;
[0064] The amino-modified nano-silica and the curing agent are mixed, the mass ratio of the amino-modified nano-silica to the curing agent is 67:395, and the mixture is stirred at a stirring speed of 300 r / min for 50 min to obtain component B;
[0065] Wherein, the amino-modified nano-silica is prepared by the following steps:
[0066] Add N-2-aminoethyl-3-aminopropyltrimethoxysilane to a 90wt% ethanol aqueous solution, add 1mol / L acetic acid aqueous solution to adjust the pH value to 4, add nano-silica, the mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane, ethanol aqueous solution, and nano-silica is 55:275:60, react at 70°C for 4h, filter after the reaction, wash with ethanol 3 times, and dry in a 50°C vacuum drying oven for 24h to obtain amino-modified nano-silica;
[0067] The curing agent is prepared by the following steps:
[0068] Triethylenetetramine and dicyclohexylcarbodiimide were stirred at a stirring speed of 150 r / min for 30 min, and then oleic acid was added, the molar ratio of triethylenetetramine, dicyclohexylcarbodiimide and oleic acid was 1.2:1:1.1, and the mixture was reacted at 40°C for 4 h under nitrogen protection. After the reaction was completed, 10 times the mass of tetrahydrofuran at 0°C was added to the reaction mixture, and the mixture was stirred at a stirring speed of 150 r / min for 30 min, and then filtered. The filtrate was rotary evaporated at 35°C to remove tetrahydrofuran to obtain a curing agent;
[0069] Component A and component B are mixed and stirred before use. The stirring condition is stirring at a stirring speed of 300 r / min for 4 minutes. The mass ratio of component A to component B is 2:1.
[0070] Example 4
[0071] This embodiment discloses a method for preparing an inorganic nanocomposite coating material for anti-corrosion in a splash zone, comprising the following steps:
[0072] Step 1, adding dodecafluoroheptyl methacrylate, dimethyl vinyl phosphate, and dibenzoyl peroxide to ethyl acetate, wherein the mass ratio of dodecafluoroheptyl methacrylate, dimethyl vinyl phosphate, dibenzoyl peroxide, and ethyl acetate is 39:14:6:240, and stirring and dispersing at a stirring speed of 150 r / min for 30 minutes to obtain a mixed solution;
[0073] Add liquid epoxy resin to ethyl acetate, stir and disperse for 30 minutes at a stirring speed of 150r / min, and then heat to 110°C under nitrogen protection, and drop the mixed solution. The mass ratio of liquid epoxy resin, ethyl acetate and mixed solution is 910:600:600. The dropwise addition time of the mixed solution is 60 minutes. After the dropwise addition is completed, react at 110°C for 3.5 hours under nitrogen protection. After the reaction is completed, remove ethyl acetate by rotary evaporation at 55°C to obtain a modified liquid epoxy resin;
[0074] Step 2: Mix the modified liquid epoxy resin and the carboxyl-terminated liquid nitrile rubber, react at 150° C. for 3 hours, cool to room temperature after the reaction, add polypropylene glycol diglycidyl ether, the mass ratio of the modified liquid epoxy resin, the carboxyl-terminated liquid nitrile rubber, and the polypropylene glycol diglycidyl ether is 950:160:220, stir at a stirring speed of 300 r / min for 50 minutes, and obtain component A;
[0075] The amino-modified nano-silica and the curing agent are mixed, the mass ratio of the amino-modified nano-silica to the curing agent is 67.5:410, and the mixture is stirred at a stirring speed of 300 r / min for 50 min to obtain component B;
[0076] Wherein, the amino-modified nano-silica is prepared by the following steps:
[0077] N-2-aminoethyl-3-aminopropyltrimethoxysilane was added to a 90wt% ethanol aqueous solution, 1 mol / L acetic acid aqueous solution was added to adjust the pH value to 4, nano-silica was added, the mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane, ethanol aqueous solution and nano-silica was 60:300:60, and the reaction was carried out at 70°C for 4h. After the reaction was completed, the mixture was filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 24h to obtain amino-modified nano-silica;
[0078] The curing agent is prepared by the following steps:
[0079] Triethylenetetramine and dicyclohexylcarbodiimide were stirred at a stirring speed of 150 r / min for 30 min, and then oleic acid was added, the molar ratio of triethylenetetramine, dicyclohexylcarbodiimide and oleic acid was 1.25:1:1.2, and the mixture was reacted at 40°C for 4 h under nitrogen protection. After the reaction was completed, 10 times the mass of tetrahydrofuran of the reaction mixture at 0°C was added to the reaction mixture, and the mixture was stirred at a stirring speed of 150 r / min for 30 min, and then filtered. The filtrate was rotary evaporated at 35°C to remove tetrahydrofuran to obtain a curing agent;
[0080] Component A and component B are mixed and stirred before use. The stirring condition is stirring at a stirring speed of 300 r / min for 4 minutes. The mass ratio of component A to component B is 2:1.
[0081] Component A and component B are mixed and stirred before use. The stirring condition is stirring at a stirring speed of 300 r / min for 4 minutes. The mass ratio of component A to component B is 2:1.
[0082] Example 5
[0083] This embodiment discloses a method for preparing an inorganic nanocomposite coating material for anti-corrosion in a splash zone, comprising the following steps:
[0084] Step 1, adding dodecafluoroheptyl methacrylate, dimethyl vinyl phosphate, and dibenzoyl peroxide to ethyl acetate, wherein the mass ratio of dodecafluoroheptyl methacrylate, dimethyl vinyl phosphate, dibenzoyl peroxide, and ethyl acetate is 41:14.5:6:260, and stirring and dispersing at a stirring speed of 150 r / min for 30 minutes to obtain a mixed solution;
[0085] Add liquid epoxy resin to ethyl acetate, stir and disperse for 30 minutes at a stirring speed of 150r / min, and then heat to 110°C under nitrogen protection, and drop the mixed solution. The mass ratio of liquid epoxy resin, ethyl acetate and mixed solution is 940:650:600, and the dropwise addition time of the mixed solution is 60 minutes. After the dropwise addition is completed, react at 110°C for 3.5 hours under nitrogen protection. After the reaction is completed, remove ethyl acetate by rotary evaporation at 55°C to obtain a modified liquid epoxy resin;
[0086] Step 2: Mix the modified liquid epoxy resin and the carboxyl-terminated liquid nitrile rubber, react at 150° C. for 3 hours, cool to room temperature after the reaction, add polypropylene glycol diglycidyl ether, the mass ratio of the modified liquid epoxy resin, the carboxyl-terminated liquid nitrile rubber, and the polypropylene glycol diglycidyl ether is 990:160:230, stir at a stirring speed of 300 r / min for 50 minutes, and obtain component A;
[0087] The amino-modified nano-silica and the curing agent are mixed, the mass ratio of the amino-modified nano-silica to the curing agent is 68:425, and stirred at a stirring speed of 300 r / min for 50 minutes to obtain component B;
[0088] Wherein, the amino-modified nano-silica is prepared by the following steps:
[0089] N-2-aminoethyl-3-aminopropyltrimethoxysilane was added to a 90wt% ethanol aqueous solution, 1 mol / L acetic acid aqueous solution was added to adjust the pH value to 4, nano-silica was added, the mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane, ethanol aqueous solution and nano-silica was 60:300:60, and the reaction was carried out at 70°C for 4h. After the reaction was completed, the mixture was filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 24h to obtain amino-modified nano-silica;
[0090] The curing agent is prepared by the following steps:
[0091] Triethylenetetramine and dicyclohexylcarbodiimide were stirred at a stirring speed of 150 r / min for 30 min, and then oleic acid was added, the molar ratio of triethylenetetramine, dicyclohexylcarbodiimide and oleic acid was 1.3:1:1.2, and the mixture was reacted at 40°C for 4 h under nitrogen protection. After the reaction was completed, 10 times the mass of tetrahydrofuran at 0°C was added to the reaction mixture, and the mixture was stirred at a stirring speed of 150 r / min for 30 min, and then filtered. The filtrate was rotary evaporated at 35°C to remove tetrahydrofuran to obtain a curing agent;
[0092] Component A and component B are mixed and stirred before use. The stirring condition is stirring at a stirring speed of 300 r / min for 4 minutes. The mass ratio of component A to component B is 2:1.
[0093] Component A and component B are mixed and stirred before use. The stirring condition is stirring at a stirring speed of 300 r / min for 4 minutes. The mass ratio of component A to component B is 2:1.
[0094] Example 6
[0095] Step 1, adding dodecafluoroheptyl methacrylate, dimethyl vinyl phosphate, and dibenzoyl peroxide to ethyl acetate, wherein the mass ratio of dodecafluoroheptyl methacrylate, dimethyl vinyl phosphate, dibenzoyl peroxide, and ethyl acetate is 43:15:6.5:280, and stirring and dispersing at a stirring speed of 150 r / min for 30 minutes to obtain a mixed solution;
[0096] Add liquid epoxy resin to ethyl acetate, stir and disperse for 30 minutes at a stirring speed of 150r / min, and then heat to 110°C under nitrogen protection, and drop the mixed solution. The mass ratio of liquid epoxy resin, ethyl acetate and mixed solution is 970:700:650, and the dropwise addition time of the mixed solution is 60 minutes. After the dropwise addition is completed, react at 110°C for 3.5 hours under nitrogen protection. After the reaction is completed, remove ethyl acetate by rotary evaporation at 55°C to obtain a modified liquid epoxy resin;
[0097] Step 2: Mix the modified liquid epoxy resin and the carboxyl-terminated liquid nitrile rubber, react at 150° C. for 3 hours, cool to room temperature after the reaction, add polypropylene glycol diglycidyl ether, the mass ratio of the modified liquid epoxy resin, the carboxyl-terminated liquid nitrile rubber, and the polypropylene glycol diglycidyl ether is 1030:165:240, stir at a stirring speed of 300 r / min for 50 minutes, and obtain component A;
[0098] The amino-modified nano-silica and the curing agent are mixed, the mass ratio of the amino-modified nano-silica to the curing agent is 69:440, and the mixture is stirred at a stirring speed of 300 r / min for 50 min to obtain component B;
[0099] Wherein, the amino-modified nano-silica is prepared by the following steps:
[0100] Add N-2-aminoethyl-3-aminopropyltrimethoxysilane to a 90wt% ethanol aqueous solution, add 1mol / L acetic acid aqueous solution to adjust the pH value to 4, add nano-silica, the mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane, ethanol aqueous solution, and nano-silica is 65:330:60, react at 70°C for 4h, filter after the reaction, wash with ethanol 3 times, and dry in a 50°C vacuum drying oven for 24h to obtain amino-modified nano-silica;
[0101] The curing agent is prepared by the following steps:
[0102] Triethylenetetramine and dicyclohexylcarbodiimide were stirred at a stirring speed of 150 r / min for 30 min, and then oleic acid was added, the molar ratio of triethylenetetramine, dicyclohexylcarbodiimide and oleic acid was 1.4:1:1.25, and the mixture was reacted at 40°C for 4 h under nitrogen protection. After the reaction was completed, 10 times the mass of tetrahydrofuran at 0°C was added to the reaction mixture, and the mixture was stirred at a stirring speed of 150 r / min for 30 min, and then filtered. The filtrate was rotary evaporated at 35°C to remove tetrahydrofuran to obtain a curing agent;
[0103] Component A and component B are mixed and stirred before use. The stirring condition is stirring at a stirring speed of 300 r / min for 4 minutes. The mass ratio of component A to component B is 2:1.
[0104] Comparative Example 1
[0105] This comparative example discloses a method for preparing an inorganic nanocomposite coating material for anti-corrosion in a splash zone, comprising the following steps:
[0106] Step 1, adding dodecafluoroheptyl methacrylate and dibenzoyl peroxide to ethyl acetate, wherein the mass ratio of dodecafluoroheptyl methacrylate, dibenzoyl peroxide and ethyl acetate is 35:5:213, and stirring and dispersing at a stirring speed of 150 r / min for 30 minutes to obtain a mixed solution;
[0107] Add liquid epoxy resin to ethyl acetate, stir and disperse at a stirring speed of 150r / min for 30min, and then heat to 100°C under nitrogen protection, and drop the mixed solution. The mass ratio of liquid epoxy resin, ethyl acetate and mixed solution is 850:500:500. The dropwise addition time of the mixed solution is 40min. After the dropwise addition is completed, react at 100°C for 4h under nitrogen protection. After the reaction is completed, remove ethyl acetate by rotary evaporation at 55°C to obtain a modified liquid epoxy resin;
[0108] Step 2: Mix the modified liquid epoxy resin and the carboxyl-terminated liquid nitrile rubber, react at 140° C. for 3.5 hours, cool to room temperature after the reaction, add polypropylene glycol diglycidyl ether, the mass ratio of the modified liquid epoxy resin, the carboxyl-terminated liquid nitrile rubber, and the polypropylene glycol diglycidyl ether is 900:150:200, stir at a stirring speed of 150 r / min for 60 minutes, and obtain component A;
[0109] The amino-modified nano-silica and the curing agent are mixed, the mass ratio of the amino-modified nano-silica to the curing agent is 66:380, and the mixture is stirred at a stirring speed of 150 r / min for 60 min to obtain component B;
[0110] Wherein, the amino-modified nano-silica is prepared by the following steps:
[0111] Add N-2-aminoethyl-3-aminopropyltrimethoxysilane to a 90wt% ethanol aqueous solution, add 1mol / L acetic acid aqueous solution to adjust the pH value to 3, add nano-silica, the mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane, ethanol aqueous solution, and nano-silica is 50:250:60, react at 60°C for 5h, filter after the reaction, wash with ethanol 3 times, and dry in a 50°C vacuum drying oven for 24h to obtain amino-modified nano-silica;
[0112] The curing agent is prepared by the following steps:
[0113] Triethylenetetramine and dicyclohexylcarbodiimide were stirred at a stirring speed of 150 r / min for 30 min, and then oleic acid was added, the molar ratio of triethylenetetramine, dicyclohexylcarbodiimide and oleic acid was 1.1:1:1, and the mixture was reacted at 30°C for 5 h under nitrogen protection. After the reaction was completed, 10 times the mass of tetrahydrofuran at 0°C was added to the reaction mixture, and the mixture was stirred at a stirring speed of 150 r / min for 30 min, and then filtered. The filtrate was rotary evaporated at 35°C to remove tetrahydrofuran to obtain a curing agent;
[0114] Component A and component B are mixed and stirred before use. The stirring condition is stirring at a stirring speed of 250 r / min for 5 minutes. The mass ratio of component A to component B is 2:1.
[0115] Comparative Example 2
[0116] This comparative example discloses a method for preparing an inorganic nanocomposite coating material for anti-corrosion in a splash zone, comprising the following steps:
[0117] Step 1, adding dodecafluoroheptyl methacrylate, vinyl dimethyl phosphate, and dibenzoyl peroxide to ethyl acetate, wherein the mass ratio of dodecafluoroheptyl methacrylate, vinyl dimethyl phosphate, dibenzoyl peroxide, and ethyl acetate is 35:13:5:200, and stirring and dispersing at a stirring speed of 150 r / min for 30 minutes to obtain a mixed solution;
[0118] Add liquid epoxy resin to ethyl acetate, stir and disperse at a stirring speed of 150r / min for 30min, and then heat to 100°C under nitrogen protection, and drop the mixed solution. The mass ratio of liquid epoxy resin, ethyl acetate and mixed solution is 850:500:500. The dropwise addition time of the mixed solution is 40min. After the dropwise addition is completed, react at 100°C for 4h under nitrogen protection. After the reaction is completed, remove ethyl acetate by rotary evaporation at 55°C to obtain a modified liquid epoxy resin;
[0119] Step 2: Mix the modified liquid epoxy resin and the carboxyl-terminated liquid nitrile rubber, react at 140° C. for 3.5 hours, cool to room temperature after the reaction, add polypropylene glycol diglycidyl ether, the mass ratio of the modified liquid epoxy resin, the carboxyl-terminated liquid nitrile rubber, and the polypropylene glycol diglycidyl ether is 900:150:200, stir at a stirring speed of 150 r / min for 60 minutes, and obtain component A;
[0120] Nano-silicon dioxide and a curing agent are mixed, with a mass ratio of nano-silicon dioxide to curing agent of 66:380, and stirred at a stirring speed of 150 r / min for 60 min to obtain component B;
[0121] The curing agent is prepared by the following steps:
[0122] Triethylenetetramine and dicyclohexylcarbodiimide were stirred at a stirring speed of 150 r / min for 30 min, and then oleic acid was added, the molar ratio of triethylenetetramine, dicyclohexylcarbodiimide and oleic acid was 1.1:1:1, and the mixture was reacted at 30°C for 5 h under nitrogen protection. After the reaction was completed, 10 times the mass of tetrahydrofuran at 0°C was added to the reaction mixture, and the mixture was stirred at a stirring speed of 150 r / min for 30 min, and then filtered. The filtrate was rotary evaporated at 35°C to remove tetrahydrofuran to obtain a curing agent;
[0123] Component A and component B are mixed and stirred before use. The stirring condition is stirring at a stirring speed of 250 r / min for 5 minutes. The mass ratio of component A to component B is 2:1.
[0124] Comparative Example 3
[0125] This comparative example discloses a method for preparing a coating material for anti-corrosion in a splash zone, comprising the following steps:
[0126] Step 1, adding dodecafluoroheptyl methacrylate, vinyl dimethyl phosphate, and dibenzoyl peroxide to ethyl acetate, wherein the mass ratio of dodecafluoroheptyl methacrylate, vinyl dimethyl phosphate, dibenzoyl peroxide, and ethyl acetate is 35:13:5:200, and stirring and dispersing at a stirring speed of 150 r / min for 30 minutes to obtain a mixed solution;
[0127] Add liquid epoxy resin to ethyl acetate, stir and disperse at a stirring speed of 150r / min for 30min, and then heat to 100°C under nitrogen protection, and drop the mixed solution. The mass ratio of liquid epoxy resin, ethyl acetate and mixed solution is 850:500:500. The dropwise addition time of the mixed solution is 40min. After the dropwise addition is completed, react at 100°C for 4h under nitrogen protection. After the reaction is completed, remove ethyl acetate by rotary evaporation at 55°C to obtain a modified liquid epoxy resin;
[0128] Step 2: Mix the modified liquid epoxy resin and the carboxyl-terminated liquid nitrile rubber, react at 140° C. for 3.5 hours, cool to room temperature after the reaction, add polypropylene glycol diglycidyl ether, the mass ratio of the modified liquid epoxy resin, the carboxyl-terminated liquid nitrile rubber, and the polypropylene glycol diglycidyl ether is 900:150:200, stir at a stirring speed of 150 r / min for 60 minutes, and obtain component A;
[0129] Triethylenetetramine and dicyclohexylcarbodiimide were stirred at a stirring speed of 150 r / min for 30 min, and then oleic acid was added. The molar ratio of triethylenetetramine, dicyclohexylcarbodiimide and oleic acid was 1.1:1:1. The mixture was reacted at 30°C for 5 h under nitrogen protection. After the reaction was completed, 10 times the mass of tetrahydrofuran at 0°C was added to the reaction mixture. The mixture was stirred at a stirring speed of 150 r / min for 30 min, and then filtered. The filtrate was rotary evaporated at 35°C to remove tetrahydrofuran to obtain a curing agent, and the curing agent was used as component B;
[0130] Component A and component B are mixed and stirred before use. The stirring condition is stirring at a stirring speed of 350 r / min for 3 minutes. The mass ratio of component A to component B is 2:1.
[0131] In the above embodiments and comparative examples: the liquid epoxy resin is a bisphenol A type liquid epoxy resin, brand: E-51, epoxy equivalent (g / eg): 180-200, purchased from Wuxi Xihua Chemical Technology Co., Ltd.; the carboxyl-terminated liquid nitrile rubber is purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., item number: P20220509, and the average molecular weight is 10000; polypropylene glycol diglycidyl ether is purchased from Shanghai Yueyi Chemical Co., Ltd., item number: YYPG-207, epoxy value (mol / 100g): 0.28-0.34; nano-silicon dioxide is purchased from Shanghai Naio Nano Technology Co., Ltd., particle size: 100nm.
[0132] Test Case
[0133] The properties of the composite coating materials obtained in Examples 1-6 and Comparative Examples 1-3 were measured:
[0134] (1) Curing and drying time: The composite coating materials prepared in Examples 1-6 and Comparative Examples 1-3 were coated on the surface of the steel plate with a coating thickness of 50 μm. The curing and drying time of the coating at a temperature of 25±1° C. was measured with reference to the standard GB / T1728-2020 “Determination of drying time of paint film and putty film”. The measurement results are shown in Table 1:
[0135] Table 1
[0136]
[0137] As shown in Table 1, the composite coating material prepared by the present invention can be cured quickly at room temperature. The curing agent in the B component is prepared by reacting aliphatic polyamines with oleic acid. The aliphatic polyamines contained in the curing agent molecules have high reactivity with epoxy groups and can react with epoxy resins at room temperature to cure epoxy resins. In addition, amino-modified nano-silicon dioxide also contains aliphatic amines, which can also participate in the low-temperature curing cross-linking reaction of epoxy resin reflection, and the drying time is short. Compared with Example 1, in Comparative Example 1, vinyl dimethyl phosphate is not added when preparing component A, which will not affect the curing cross-linking reaction of the coating material and has no effect on the curing drying time. In Comparative Example 2, the nano-silicon dioxide is not subjected to amino modification treatment, and there is no aliphatic amine introduced by the amino coupling agent, so the curing cross-linking effect on the epoxy resin is weakened, and the curing drying time is increased. In Comparative Example 3, the aliphatic amine introduced by the amino coupling agent is also lacking, and the curing drying time is also increased.
[0138] (2) Adhesion: The composite coating materials prepared in Examples 1-6 and Comparative Examples 1-3 were coated on the surface of the steel plate with a coating thickness of 50 μm. After curing and drying at room temperature for 24 hours, the adhesion of the coating was measured with reference to the standard GB / T5210-2006 "Adhesion test of paint and varnish by pull-off method". The measurement results are shown in Table 2:
[0139] Table 2
[0140]
[0141] As shown in Table 2, the composite coating material prepared by the present invention has excellent adhesion. The present invention uses epoxy resin as a film-forming material, which itself has good adhesion. The introduced organic phosphate vinyl dimethyl phosphate can further improve the adhesion of the composite coating material. Compared with Example 1, in Comparative Example 1, vinyl dimethyl phosphate was not added when preparing component A, and the adhesion of the coating decreased significantly. In Comparative Example 2, nano-silicon dioxide was not subjected to amino modification treatment, and in Comparative Example 3, nano-silicon dioxide was not added, which did not have a significant effect on the adhesion of the coating.
[0142] (3) Impact resistance: The composite coating materials prepared in Examples 1-6 and Comparative Examples 1-3 were coated on the surface of the steel plate with a coating thickness of 50 μm. After curing and drying at room temperature for 24 h, the impact strength of the coating was measured with reference to the standard GB / T1732-2020 "Determination of impact resistance of paint film". The measurement results are shown in Table 3:
[0143] Table 3
[0144]
[0145] As shown in Table 3, the composite coating material prepared by the present invention has good impact resistance. In the present invention, by introducing carboxyl-terminated liquid nitrile rubber into epoxy resin, the toughness of the composite coating material can be improved, and then the impact resistance of the coating can be improved. In addition, polypropylene glycol diglycidyl ether with a flexible molecular chain is added as an epoxy resin active diluent, which can also improve the impact resistance of the coating. Finally, the addition of inorganic nanomaterials can not only improve the anti-corrosion performance of the coating, but also improve the strength and toughness of the coating, and further enhance the impact resistance. Compared with Example 1, in Comparative Example 1, vinyl dimethyl phosphate is not added when preparing component A, and the impact resistance of the coating is not significantly affected. In Comparative Example 2, nano silicon dioxide is not subjected to amino modification treatment, and the curing cross-linking effect with epoxy resin is weakened, and the impact resistance is reduced. In Comparative Example 3, nano silicon dioxide is not added, and the impact resistance is significantly reduced.
[0146] (4) Neutral salt spray resistance: The composite coating materials prepared in Examples 1-6 and Comparative Examples 1-3 were coated on the surface of steel plates with a coating thickness of 50 μm. After curing and drying at room temperature for 24 h, the neutral salt spray resistance of the coated steel plates was tested with reference to the standard GB / T1771-2007 "Paints and varnishes, determination of neutral salt spray resistance". The steel samples were placed in a salt spray chamber with the coating facing upward and the angle with the vertical being 20°. The temperature of the salt spray chamber was 35°C and the salt spray pressure was 1 kg / cm 2, gas source is 5kg / cm 2 , use atomized 5wt% NaCl aqueous solution to spray periodically and continuously, observe and record the time when corrosion begins to appear. The test results are shown in Table 4:
[0147] Table 4
[0148]
[0149] As shown in Table 4, the composite coating material prepared by the present invention has good anti-corrosion performance and can effectively resist the corrosion of smoke. The present invention uses epoxy resin as a film-forming material, which itself has good anti-corrosion performance. The addition of dodecafluoroheptyl methacrylate can improve the hydrophobicity of the composite coating material and reduce the erosion of the coating by salt water. The addition of vinyl dimethyl phosphate can improve the adhesion of the coating material, prevent smoke from penetrating from the loose part of the coating, and accelerate the corrosion of the steel plate. The addition of nano-silicon dioxide can extend the corrosion path and reduce the corrosion rate. Compared with Example 1, in Comparative Example 1, vinyl dimethyl phosphate was not added when preparing component A, the adhesion of the coating was reduced, and the anti-corrosion performance was reduced. In Comparative Example 2, nano-silicon dioxide was not subjected to amino modification treatment, and the curing and cross-linking effect with epoxy resin was weakened, and the anti-corrosion performance was reduced. In Comparative Example 3, nano-silicon dioxide was not added, and the anti-corrosion performance was significantly reduced.
[0150] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An inorganic nanocomposite coating material for anti-corrosion in splash zone, comprising component A and component B, characterized in that: Prepared by the following method: Step 1, adding dodecafluoroheptyl methacrylate, dimethyl vinyl phosphate and dibenzoyl peroxide into ethyl acetate, stirring and dispersing to obtain a mixed solution; Add liquid epoxy resin to ethyl acetate, stir and disperse, raise the temperature to a set temperature under the protection of inert gas, drop the mixed solution, react after the dropwise addition, and rotary evaporate after the reaction to obtain a modified liquid epoxy resin; Step 2: Mix the modified liquid epoxy resin and the carboxyl-terminated liquid nitrile rubber, react, cool to room temperature after the reaction is completed, add polypropylene glycol diglycidyl ether, stir, and obtain component A; The amino-modified nano-silica is mixed with the curing agent and stirred to obtain component B; Wherein, the curing agent is prepared by the following steps: Aliphatic polyamine and dicyclohexylcarbodiimide are stirred, and then oleic acid is added to react. After the reaction is completed, the reaction is purified to obtain a curing agent.
2. The method for preparing an inorganic nanocomposite coating material for splash zone corrosion protection according to claim 1, characterized in that: In the step 1: when preparing the mixed solution, the mass ratio of dodecafluoroheptyl methacrylate, dimethyl vinyl phosphate, dibenzoyl peroxide and ethyl acetate is (35-45):(13-16):(5-7):(200-300).
3. The method for preparing an inorganic nanocomposite coating material for splash zone corrosion protection according to claim 1, characterized in that: In the step 1: when preparing the modified liquid epoxy resin, the mass ratio of the liquid epoxy resin, ethyl acetate and the mixed liquid is (850-1000):(500-750):(500-700), and the dripping time of the mixed liquid is 40-60 minutes.
4. The method for preparing an inorganic nanocomposite coating material for splash zone corrosion protection according to claim 1, characterized in that: In the step 1, the reaction conditions are to react for 3-4 hours under the protection of an inactive gas at a set temperature, wherein the set temperature is 100-120°C.
5. The method for preparing an inorganic nanocomposite coating material for splash zone corrosion protection according to claim 1, characterized in that: In the step 2, when preparing component A, the mass ratio of the modified liquid epoxy resin, the carboxyl-terminated liquid nitrile rubber, and the polypropylene glycol diglycidyl ether is (900-1060):(150-170):(200-250), and the reaction conditions are to react at a temperature of 140-160° C. for 2.5-3.5 hours; and the stirring conditions are to stir at a stirring speed of 250-350 r / min for 40-60 minutes.
6. The method for preparing an inorganic nanocomposite coating material for splash zone corrosion protection according to claim 1, characterized in that: In the step 2, when preparing component B, the mass ratio of amino-modified nano-silica to curing agent is (66-70):(380-460), and the stirring condition is stirring at a stirring speed of 150-250 r / min for 40-60 min.
7. The method for preparing an inorganic nanocomposite coating material for splash zone corrosion protection according to claim 1, characterized in that: The component A and the component B prepared in the step 2 are mixed and stirred before use. The stirring condition is stirring at a stirring speed of 250-350 r / min for 3-5 min. The mass ratio of component A to component B is 2:
1.
8. The method for preparing an inorganic nanocomposite coating material for splash zone corrosion protection according to claim 1, characterized in that: The amino-modified nano-silica in step 2 is prepared by the following steps: Add N-2-aminoethyl-3-aminopropyltrimethoxysilane to an ethanol aqueous solution, adjust the pH value to 3-5, add nano-silicon dioxide, react, filter, wash, and dry after the reaction to obtain amino-modified nano-silicon dioxide; The mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane, ethanol aqueous solution and nano-silicon dioxide is (50-70):(250-350):60, and the reaction conditions are 60-80° C. for 3-5 hours.
9. The method for preparing an inorganic nanocomposite coating material for splash zone corrosion protection according to claim 1, characterized in that: In the step 2, when preparing the curing agent, the molar ratio of aliphatic polyamine, dicyclohexylcarbodiimide and oleic acid is (1.1-1.5):1:(1-1.3), and the reaction conditions are to react at a temperature of 30-50° C. for 3-5 hours under the protection of an inert gas.
10. An inorganic nano-composite coating material for use in splash zone corrosion protection prepared by the method for preparing an inorganic nano-composite coating material for use in splash zone corrosion protection according to any one of claims 1 to 9.
Citation Information
Patent Citations
A long-lasting anti-corrosion and weather-resistant functional coating and its preparation method
CN108841289B
Cited By
High-strength rain-erosion-resistant coating and preparation method thereof
CN120924138A
High-strength rain-erosion-resistant coating and preparation method thereof
CN120924138B